2004
DOI: 10.5032/jae.2004.02039
|View full text |Cite
|
Sign up to set email alerts
|

Global Perspectives and Attitudes Toward Cultural Diversity Among Summer Agriculture Students at the Ohio State University

Abstract: The purpose of this study was to measure the level of global perspective and attitude toward cultural diversity among summer agriculture students using established survey scales for these constructs. A survey instrument was completed by 145 agriculture students at The Ohio State University. Survey results indicated that, in general, students tended to have a moderate global perspective and a positive attitude toward cultural diversity. High correlation was also found between global perspectives and attitudes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 15 publications
6
42
1
2
Order By: Relevance
“…Examples include its application to the Thai socio-cultural context (Lawthong, 2003), the use of the scale in measuring the effects of study abroad programs (Kehl & Morris, 2008) and the interesting combination of Hett's scale with Stanley's Attitudes towards Cultural Diversity and Pluralism test in a research study focusing on Ohio agriculture students (Stanley, 1996;Zhai & Scheer, 2004).…”
Section: World-mindednessmentioning
confidence: 99%
“…Examples include its application to the Thai socio-cultural context (Lawthong, 2003), the use of the scale in measuring the effects of study abroad programs (Kehl & Morris, 2008) and the interesting combination of Hett's scale with Stanley's Attitudes towards Cultural Diversity and Pluralism test in a research study focusing on Ohio agriculture students (Stanley, 1996;Zhai & Scheer, 2004).…”
Section: World-mindednessmentioning
confidence: 99%
“…Hett's (1993) study suggested that women would score higher on the GMS than men. Zhai and Scheer's (2004) study stated that female students are more sensitive toward global issues.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 148) Applying the GMS as a research tool, Hett (1993) confirmed a variety of hypotheses she generated from a literature review: (a) Women score higher on the GMS than men, (b) there is a significant correlation between the number of global study courses learned and global-mindedness, (c) there is a significant difference in the global-mindedness scores between students who attend internationally oriented programs frequently and those who do not, (d) students who report their political attitude as more liberal score higher than those who say they are more conservative, (e) students with two or more of their friends from countries or cultures other than their own score higher than students with fewer than two such friends, (f) second language proficiency is slightly related to global-mindedness, and (g) there is a significant difference in GMS between students with different levels of international experience. Zhai and Scheer (2004) conducted a quantitative study on undergraduate students declaring agriculture majors in the College of Food, Agriculture, and Environment Sciences at OSU. Zhai and Scheer combined an adapted GMS with the Attitudes Towards Cultural Diversity and Pluralism Scale to use as a survey instrument.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…However, there are also statements that are somewhat similar: Sampson and Smith's 'Our country should not cooperate in any international trade agreements which attempt to better world economic conditions at our expense' corresponds to Hett's 'The needs of the United States must continue to be our highest priority in negotiating with other countries' (both reverse statements). Like Sampson and Smith's world-mindedness scale, Hett's global-mindedness scale has been applied and tested in research by others (Lawthong, 2003;Zhai and Scheer, 2004;Kehl and Morris, 2007;DeMello, 2011).…”
Section: … a Value Orientation Or Frame Of Reference Apart From Knomentioning
confidence: 99%